Heterogeneity of Graphite Lithiation in State‐of‐the‐Art Cylinder‐Type Li‐Ion Cells. Issue 2 (1st February 2021) - Petz, Dominik; Mühlbauer, Martin J.; Schökel, Alexander; Achterhold, Klaus; Pfeiffer, Franz; Pirling, Thilo; Hofmann, Michael; Senyshyn, Anatoliy
Abstract: Invited for this month's cover picture is the group of Anatoliy Senyshyn. The cover picture displays the lithium distribution in the graphite anode of an 18650‐type Li‐ion battery. A look into the cell's interior illustrates a non‐destructive character of the performed studies. The background template corresponds to the structure of lithiated graphite, referring to the diffraction technique as a tool for spatially resolved quantification of lithium concentration within the cell. Read the full text of the Article at 10.1002/batt.202000178 . Abstract : "Using spatially resolved neutron diffraction, the 2D lithium distribution in the graphite anode was non‐destructively probed for a batch of cylinder‐type (18650) Li − ion batteries in fully charged state. Peculiarities of lithium distribution were correlated to the cell specifications/electrochemistry and to intrinsic cell parameters like electrode thickness, position of current collectors, etc., which were obtained by X‐ray micro‐computed tomography. A method for quantification and comparison of non‐uniformities in the lithiation of the graphite anode is proposed…." Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article on 10.1002/batt.202000178 .